2018
DOI: 10.1016/j.watres.2018.07.039
|View full text |Cite
|
Sign up to set email alerts
|

A horizontal permeable reactive barrier stimulates nitrate removal and shifts microbial ecology during rapid infiltration for managed recharge

Abstract: We present results from field experiments linking hydrology, geochemistry, and microbiology during infiltration at a field site that is used for managed aquifer recharge (MAR). These experiments measured how a horizontal permeable reactive barrier (PRB) made of woodchips impacted subsurface nitrate removal and microbial ecology. Concentrations of dissolved organic carbon consistently increased in infiltrating water below the PRB, but not in un-amended native soil. The average nitrate removal rate in soils belo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 70 publications
(83 reference statements)
5
34
0
Order By: Relevance
“…For example, a PRB made of vegetal compost and woodchips was installed in an MAR system to promote denitrification during infiltration of diverted river water, resulting in 30–40% nitrogen removal on some days but negligible removal or addition on other days . Controlled percolation experiments using water with elevated [NO 3 ] demonstrated that adding a woodchip PRB to coarse-grained soils (>90% sand) led to enhanced denitrification during rapid infiltration . This study also noted a negative correlation between rates of infiltration and denitrification, with tests run at infiltration rates up to 1.9 m/day.…”
Section: Introductionmentioning
confidence: 66%
“…For example, a PRB made of vegetal compost and woodchips was installed in an MAR system to promote denitrification during infiltration of diverted river water, resulting in 30–40% nitrogen removal on some days but negligible removal or addition on other days . Controlled percolation experiments using water with elevated [NO 3 ] demonstrated that adding a woodchip PRB to coarse-grained soils (>90% sand) led to enhanced denitrification during rapid infiltration . This study also noted a negative correlation between rates of infiltration and denitrification, with tests run at infiltration rates up to 1.9 m/day.…”
Section: Introductionmentioning
confidence: 66%
“…Similarly, in situ amendments for infiltration basins have been proposed, including addition of carbon sources (e.g., wood chips) to create a horizontal permeable reactive barrier and promote denitrifying conditions. These studies focus on nitrate removal from recharge water during infiltration and associated shifts in microbial community structure. While nitrate is a primary contaminant, preventing nitrate from reaching deeper groundwater supplies can also minimize the potential for oxidation of reduced immobile geogenic contaminant phases (e.g., arsenian pyrite, uraninite) limiting mobilization potential along the flow path.…”
Section: Water Quality Considerations For the Future Of Marmentioning
confidence: 99%
“…The addition of reactive barriers has shown promising results for the removal of organic micropollutants and for reducing the number of pathogens in the treated water ( Schaffer et al, 2015 ; Valhondo et al, 2020a ; Modrzyński et al, 2021 ). With respect to nitrogen (N) removal, reactive barriers can also support denitrification for the removal of nitrate ions ( Beganskas et al, 2018 ; Grau-Martínez et al, 2018 ). However, the fate of N when ammonium-rich treated sewage water is used with compost as a reactive layer has not yet been well addressed and may even counteract the desired N removal ( Modrzyński et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%